PENGARUH MODAL KERJA, KEBIJAKAN DIVIDEN, DAN ROA TERHADAP NILAI PERUSAHAAN DENGAN HARGA SAHAM SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BEI PADA TAHUN 2019-2022 - Widiyanto, Ahmad Irfan; Pramitasari, Triska Dewi; Subaida, Ida (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The aim of the research is to analyze and test the influence of working capital, dividend policy and ROA on company value through share prices. The populations in this study are pharmaceutical sector companies listed on the IDX in 2019-2022. The sampling technique used is non-probability sampling using purposive sampling technique. The data analysis and hypothesis testing in this research used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of direct hypothesis testing show that capital working capital has no significant effect on stock prices, the profitability has a significant effect on stock prices, the company size has no significant effect on stock prices, the capital structure has no significant effect on company value, the profitability has no significant effect on company value, and the company size has significant effect on company value. The results of the indirect influence hypothesis test show that capital structure has no significant effect on company value through share prices, the profitability has no significant effect on company value through share prices, and the company size has no significant effect on company value through share prices.